AI-Driven DevOps Practices for Healthcare Data Security and Compliance - Vemuri , Naveen (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The healthcare industry is rapidly adopting cloud-based solutions to leverage benefits such as scalability, cost-efficiency, and accessibility. However, ensuring the security and compliance of sensitive patient health information in the cloud remains a major concern. This paper explores how artificial intelligence (AI)-driven DevOps practices can enable robust security and compliance for healthcare data in cloud environments. Various techniques like infrastructure-as-code, continuous monitoring, AIOps, and machine learning-powered automation are discussed. Challenges such as lack of security expertise, complex regulatory policies, and scalability needs are addressed. Best practices around access controls, network segmentation, encryption, auditing, and compliance validation are suggested. The paper concludes by proposing an AI-driven DevOps framework tailored for healthcare industry needs. The use of emerging technologies like containers, microservices, and policy-as-code in conjunction with AI and ML can lead to proactive, adaptive, and autonomic security and compliance of healthcare cloud infrastructure.